Pulmonary Immune-Compartment-Specific Interferon Gamma Responses in HIV-Infected Individuals with Active Tuberculosis (TB) in an Area of High TB Prevalence - S. Buldeo; D. M. Murdoch; M. S. Suchard (Clinical and Developmental Immunology)
There is a paucity of data on the pulmonary immune-compartment interferon gamma (IFNγ) response to M. tuberculosis, particularly in settings of high tuberculosis (TB) prevalence and in HIV-coinfected individuals. This data is necessary to understand the diagnostic potential of commercially available interferon gamma release assays (IGRAs) in both the pulmonary immune-compartment and peripheral blood. We used intracellular cytokine staining by flow cytometry to assess the IFNγ response to purified protein derivative (PPD) and early secretory antigen 6 (ESAT6) in induced sputa (ISp) and blood samples from HIV-infected, smear-negative, TB suspects. We found that individuals with active TB disease produced significantly less IFNγ in response to PPD in their induced sputa samples than individuals with non-active TB (control group). This difference was not reflected in the peripheral blood, even within the CD27− CD4+ memory T lymphocyte population. These findings suggest that progression to active TB disease may be associated with the loss of IFNγ secretion at the site of primary infection. Our findings highlight the importance of studying pulmonary immune-compartment M. tuberculosis specific responses to elucidate IFNγ secretion across the spectrum of TB disease.